Sanitary Exhaustion in Abreu e Lima City: The Shocks Caused in Timbó River | Exaustão sanitária na cidade de Abreu e Lima: os choques causados ??no rio Timbó - de Santana, Jackeline Fernandes; Machado, José (Revista Geama, 2017)
A good sanitation structure for some city is connecting with health solid measure, and to guarantee a good health to the people, keeping out of water the disease. In the same time it guarantees the preservation of environment. This search showed up shortage of sanitary debility and the shocks caused with reject without treatment in Timbo River. The results indicated that the young Abreu e Lima City hadn’t been built with a sewage treatment station to treat the sewage produced at homes, before reject, only a studied district has a STS. It had been observed in studied districts that the sewage produced is illegal rejected in brook, ditch and Barro Branco River in Caetes III district, arriving in his final destiny in Timbo River estuary, causing impacts in fauna, flora in his spill. Showing up, the urgency in the governess intervention, of the environment protection institution and the population.